Mechanical and bioprosthetic valves in young women: a systematic review and meta-analysis of cardiac, maternal, and fetal outcomes - Harta, I Komang Adhi Parama; Pertiwi, Putu Febry Krisna; Yasa, Ketut Putu; Sudarma, I Wayan (Indonesian Vascular Access Association (IVAA), 2024)
Valve replacement for the heart in young women, particularly those who are pregnant, is challenging. It requires finding the right balance between valve durability, managing anticoagulation, and ensuring positive reproductive outcomes. This systematic review and meta-analysis compared mechanical prosthetic (MP) and bioprosthetic valves (BP) across cardiac, maternal, and fetal outcomes. Nine studies were included following a comprehensive literature search. The analysis revealed MACE involving MP and BP were not significantly different (OR: 1.31, 95% CI: 0.82–2.09, p = 0.26). Thromboembolic events were significantly more frequent in the MP group (OR: 6.59, 95% CI: 3.41–12.74, p < 0.001), while structural valve deterioration (SVD) occurred more often in BP recipients (OR: 0.01, 95% CI: 0.00–0.70, p = 0.03). Maternal outcomes showed a higher risk of pregnancy loss in MP recipients (OR: 4.62, 95% CI: 1.87–11.40, p < 0.001). Preterm delivery was more common went down in the MP group, but it wasn't enough to warrant statistical analysis (OR: 2.20, 95% CI: 0.86–5.58, p = 0.10). For reoperation or redo surgery, MP had lower risk and showed superior results than BP (OR: 0.06, 95% CI: 0.01–0.32, p = 0.001). These findings highlight the complexities involved in choosing between valve types. Although MP valves last longer, they increase the likelihood of thromboembolic events and miscarriage. While improving results for both the mother and the unborn child, BP valves, are prone to structural deterioration, necessitating reoperation. Individualized treatment decisions that consider patient preferences, clinical context, and reproductive plans are essential to optimizing outcomes for young women requiring valve replacement.